2001
DOI: 10.3354/meps212171
|View full text |Cite
|
Sign up to set email alerts
|

Shell wiping in Calliostoma zizyphinum: the use of pedal mucus as a provendering agent and its contribution to daily energetic requirements

Abstract: The phenomenon of shell wiping in Calliostoma zizyphinum (L.) was investigated with regard to its potential function as a feeding adaptation. It was determined that C. zizyphinum will, on average, wipe the surface of its shell with its foot twice every 24 h, in the process consuming any matter that has adhered to the pedal mucus present on the surface of its shell. Examination of the importance of shell wiping to C. zizyphinum, both as a mechanism to reduce shell fouling and as a source of nutrition, revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…Knowledge of the species-specific feeding preferences of gastropods is still scarce to have a definitive classification and different feeding-behavior can be assigned to the same species amongst studies. For example, Calliostoma zizyphinum has been considered a true carnivore that predates on colonial and sedentary animals ) but it has also been found to consume microalgae through shell wiping (Holmes et al 2011). Following Pête et al (2015), microalgae, ciliates, foraminiferans and bryozoans are expected to be present in early biofilm successional communities and so the results mentioned in the previous sentence are consistent with our results and point to a generalist feeding behaviour of C. zizyphinum.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Knowledge of the species-specific feeding preferences of gastropods is still scarce to have a definitive classification and different feeding-behavior can be assigned to the same species amongst studies. For example, Calliostoma zizyphinum has been considered a true carnivore that predates on colonial and sedentary animals ) but it has also been found to consume microalgae through shell wiping (Holmes et al 2011). Following Pête et al (2015), microalgae, ciliates, foraminiferans and bryozoans are expected to be present in early biofilm successional communities and so the results mentioned in the previous sentence are consistent with our results and point to a generalist feeding behaviour of C. zizyphinum.…”
Section: Discussionsupporting
confidence: 90%
“…) but it has also been found to consume microalgae through shell wiping (Holmes et al . ). Following Pête et al .…”
Section: Discussionmentioning
confidence: 97%
“…cue (see Raimondi, 1988 for discussion). Alternatively, the ability of pedal mucus to stimulate settlement and hence act as a provendering agent, thereby o¡setting the energetically expensive cost of its production (see Holmes et al, 2001 for discussion), would be a sensible strategy for more generalist feeding species. For such species, it is unlikely that the pedal mucus produced by them will contain a chemotaxic cue as the presence of such a cue could allow a settling organism to evolve a negative response.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis confirmed that actinobacteria are associated with the snail and are actively dividing. Snails have been known to use mucus to cover their shells (20), and mucus has been reported to contain bioactive compounds (23), indicating one of many potential roles for these bacteria. Moreover, since actinobacterial sequences in the samples were derived solely from actinomycetales, it is probable that these identified bacteria fall within this group.…”
Section: Vol 75 2009 Actinobacteria In Venomous Cone Snail Microhabmentioning
confidence: 99%